Factors Associated with Fluid Sequestration in Patients with Acute Pancreatitis: A Prospective Study in Tertiary Centre Hospital in Nepal - Raju Bhandari; Krishna Sapkota; Seema Subedi; Som Kumar Shrestha; Edward Sutanto; Prabhat Jha; Ramesh Singh Bhandari (Gastroenterology Research and Practice)
Background. Acute pancreatitis (AP) is associated with extensive fluid sequestration. The aim of this study was to determine association of fluid sequestration at 48 hours after hospital admission (FS48) in AP patients with demographics, clinical parameters, and outcomes of AP. Methods. A prospective observational study was carried out on all adult patients with AP admitted to Tribhuvan University Teaching Hospital, Nepal, from January to September 2017. FS48 was calculated as the difference between fluid input and output in the first 48 hours of admission. The Kruskal-Wallis test with post hoc Dunn’s test examined the difference in FS48 between mild AP, moderately severe AP, and severe AP. Linear regression analysis was used to evaluate association between FS48 with patients’ characteristics and outcomes of AP. Outcomes of AP assessed included pancreatic necrosis, persistent organ failure, length of stay, and in-hospital mortality. Results. Eighty patients (median age 44 years; 57% male) with a median FS48 of 1610 mL were evaluated. The median FS48 for mild AP, moderately severe AP, and severe AP were 1,180 mL, 2,380 mL, and 3,500 mL, respectively. There was a significant difference in pairwise comparisons between mild AP and moderately severe AP, along with mild AP and severe AP. Younger age, other etiology, and higher creatinine were independently associated with increased FS48. Increased FS48 was significantly associated with pancreatic necrosis, persistent organ failure, and in-hospital mortality. Conclusions. In our study population, younger age and higher creatinine were predictors of increased FS48. Increased FS48 was associated with poorer outcomes of AP.